2015
DOI: 10.1007/s00590-015-1635-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of patient quality of life scores and satisfaction after common orthopedic surgical interventions

Abstract: Patient quality of life scores are commonly used to assess patient-reported satisfaction following orthopedic interventions. Our main aim was to review the satisfaction scores of four common orthopedic interventions in our tertiary institution, primary hallux valgus (HV) corrective surgery, primary single-level transforaminal lumbar interbody fusion (TLIF), primary unilateral total knee arthroplasty (TKA) and primary total hip arthroplasty (THA). We retrospectively reviewed prospectively collected data on pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 24 publications
1
24
0
1
Order By: Relevance
“…However, we showed that the degree of satisfaction (partial and complete expectation fulfilment) reached after THA was greater than after TKA (94% vs 85%), whereas dissatisfaction was more often expressed after TKA than THA (15% vs 6%). This observation is consistent with the results of most previous studies [25, 26] but not all of them [27]. The main determinant of satisfaction was the level of preoperative expectations.…”
Section: Discussionsupporting
confidence: 93%
“…However, we showed that the degree of satisfaction (partial and complete expectation fulfilment) reached after THA was greater than after TKA (94% vs 85%), whereas dissatisfaction was more often expressed after TKA than THA (15% vs 6%). This observation is consistent with the results of most previous studies [25, 26] but not all of them [27]. The main determinant of satisfaction was the level of preoperative expectations.…”
Section: Discussionsupporting
confidence: 93%
“…Hallux valgus deformity (HV) is a very common disease, affecting about every fourth individual up to 65 years and around every third individual later on in life [ 1 ]. Patient satisfaction after HV surgery (77.4%) is lower than that in other typical orthopaedic procedures, such as total hip arthroplasty (91.9%) [ 2 ]. Thus, the search for the optimal surgical technique and causes for unsatisfactory outcomes remains of current interest.…”
Section: Introductionmentioning
confidence: 99%
“…Total joint arthroplasty (TJA) is often considered one of the success stories of modern medicine, as it provides reliable long-term improvement in patient function, pain, and quality of life. 1–8 Aseptic loosening (AL) by periprosthetic osteolysis is the leading cause of failure after TJA 4–6 , 9 , 10 with reported incidence rates ranging from 10% to 70%. 4 , 5 , 11 , 12 The incidence of TJA is increasing, with over four million primary total hip/knee arthroplasties (THA, TKA) projected annually by 2030 in the United States and revision rates expected to double even earlier.…”
Section: Introductionmentioning
confidence: 99%